Group Counseling for Fostering Resident at UPTD Social Welfare Centre (UPTD-PSRAMPK) Ogan Ilir - Yeni Anna Appulembang; Angeline Zefany Tarian; Indra Prapto Nugroho (Altifani Journal: International Journal of Community Engagement, 2024)
Social Rehabilitation is spread across several cities in Indonesia and one of them is in South Sumatra which is located in Ogan Ilir. Children included in the UPTD Children's Rehabilitation Social Home Need Special Protection (UPTD – RAMPK) from various problems. Based on the results of observations, it show that the inmates also experience psychological issues, one of which is self-esteem. The subjects showed that they had negative feelings within themselves. They consider that they cannot do something even though they have been given various activities to improve their hard skills. The problem of low self-esteem can be overcome through a group counseling approach. Group counseling can also be a therapeutic medium for individuals to improve self-understanding and behavior change. The counseling session consists of 5 stages, namely: (a) the initial stage; (b) the transition stage; (c) the working stage; (d) the termination stage; and (e) follow-up.  Subjects are also given a pretest and posttest. Based on the results of statistical data analysis using the paired sample t-test, it was found that there was a difference in scores before and after the provision of group counseling. This is shown by the mean value before group counseling of 25.10 and the mean value after group counseling of 26.60. The standard deviation value before group counseling was 1.28 and the standard deviation after group counseling was 1.95. In addition, the results of the data analysis conducted a test of the difference in a p-value of 0.048 < 0.05. This shows that there is a significant difference before and after the provision of group counseling to Assisted Residents at the UPTD Social Rehabilitation Home for Children in Need of Special Protection (RAMPK).